PWE-228 Patient and carer experiences of living with a jejunostomy feeding tube after surgery for oesophago-gastric cancer. (22nd June 2015) - Halliday, V; Baker, M; Thomas, A; Bowrey, D
Abstract : Introduction: Home jejunostomy tube feeding (JTF) can be used to support patients following oesophago-gastric surgery in order to ameliorate nutritional deficits. Previous studies have explored the effects of gastrostomy tube feeding, but little is known about the personal impact of having a JFT. The aim of this qualitative study was to explore how patients and their carers experience living with a JFT post surgery for esophago-gastric cancer. Method: Participants were purposively sampled from a cohort of patients recruited to a trial investigating home enteral nutrition versus standard care after oesophagectomy or total gastrectomy for cancer. The sampling framework considered age, gender and marital status. Partners and carers of those included were also invited to participate. Interviews were audio recorded, transcribed verbatim and anonymised. Inductive thematic data analysis involved the research team reading and re-reading the transcripts followed by initial coding and cross-checking. Sub-themes and themes were developed and then summarised. Data organisation and retrieval were managed using NVivo 10. Results: Fifteen interviews (12 men) were conducted, lasting between 21 and 75 min. Eight interviews also included a partner or carer, all of whom were female. The mean age of the patients was 65.5 years (range 52 to 74 years) and most (67%) were married or co-habiting. All patients had a JFT placed at the time of surgery which had been used in the immediate postoperative period. Eleven had received artificial feeding post-discharge from hospital (duration of feeding 28 to 104 days). Interviews were conducted 2–3 months post surgery. Two main themes were identified, (1) Challenges and (2) Motivators of living with a JFT. Within these themes "Physical side effects", "Worries" and "Impact on routine" were the main challenges, while "Support", "Adaptation" and "Perceived benefit" were what motivated continuation of the intervention. All participants identified physical and psychosocial side effects related to having a tube, but the manner in which was expressed varied. Despite this, participants described how consistently well they coped, demonstrating high levels of compliance with stoma care and the feeding regimen. Conclusion: A better understanding of the challenges of living with a JFT, and what motivates coping and compliance from the patient and carer perspective, may help health care teams provide proactive support to avoid preventable problems. Furthermore, this improved knowledge of what motivates patients to comply with a life-changing clinical intervention such as artificial feeding may provide valuable insight that can be used across other areas of health care. Disclosure of interest: V. Halliday: None Declared, M. Baker: None Declared, A. Thomas Grant/ Research Support from: Fresenius-Kabi, D. Bowrey Grant/ Research Support from: Nutricia, Fresenius-Kabi.